(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Cisplatin is one of the most widely used and most potent chemotherapy drugs. However, side effects in normal tissues and organs, notably nephrotoxicity in the kidneys, limit the use of cisplatin and related platinum-based therapeutics. Renoprotective approaches are being discovered, but the protective effects are mostly partial, suggesting the need for combinatorial strategies. The cytoprotective efficacy of Daidzein, Naringenin, and Icariin against Cisplatin-induced nephrotoxicity in female Swiss mice was examined in this work. All animals were divided into two sets i.e. pre-cisplatin (BA) and post-cisplatin (AA) administration and treated with Daidzein, Naringenin, and Icariin. Nephrotoxicity was assessed by body weight and biochemical parameters i.e. Serum Creatinine, Urea, uric acid During this study body weight of the experimental animal changed by 5% maximum observed in both sets. Biochemical tests of kidney showed that pre-treated and post-treated with Daidzein groups were most effective against nephrotoxicity. These findings are also confirmed by histopathology. The study has proven that pre-treatment with flavonoids was found more effective against cisplatin-induced cytotoxicity as compared to post-treatment.